STUDENTS’ PERCEPTION ON THE EFFECT OF ENGLISH SPEECH COMPETITION TOWARD SPEAKING SKILLS AT SMA ISTIQAMAH MUHAMMADIYAH SAMARINDA - Majid, Akhmad Nur; Khatimah, Khusnul (Universitas Muhammadiyah Makassar, 2024)
The development of speaking skills among high school students is essential for effective communication and future success. This study investigates students' perceptions of the impact of participating in English speech competitions on their speaking abilities at SMA Istiqamah Muhammadiyah Samarinda. Additionally, it explores the challenges that hinder students from maximizing the benefits of these competitions. Using a mixed-method approach, data were collected from students who participated in English competitions over the past two years. The research utilized questionnaires adapted from previous studies and semi-structured interviews to gather insights from the students. Supplementary data were obtained through documentation of students' assignments from the competitions. The findings reveal that English speech competitions significantly enhance students' speaking skills by increasing their confidence, enriching their vocabulary, and improving their pronunciation and fluency. However, factors such as limited practice opportunities, anxiety, and inadequate feedback mechanisms were identified as barriers to achieving the full benefits. This study highlights the importance of incorporating structured and supportive speech competition programs in the curriculum to foster better speaking skills among students.